Evaluation of Character Education Programs in Fostering Attitudes of Tolerance and Respect for Cultural Diversity Among Elementary School Students - Evisensia, Melati Moona (Kampret Journal, 2025)
This research evaluates the effectiveness of character education programs in fostering attitudes of tolerance and respect for cultural diversity among elementary school students. With increasing globalization and diversity in schools, it is essential to equip students with the values of empathy, respect, and appreciation for cultural differences. The study utilized a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess the impact of character education on students' attitudes towards cultural diversity. The research findings indicate that character education programs positively influence students’ perceptions of diversity, promoting greater inclusivity and respect for individuals from different cultural backgrounds. However, the study also highlights challenges such as variations in program implementation, subjectivity in measuring attitudes, and external influences like family and peer dynamics. Despite these limitations, the research demonstrates that character education is a valuable tool in shaping young minds and fostering cultural awareness. The study concludes that by integrating character education into school curricula, educators can lay the groundwork for a more tolerant, inclusive society. Recommendations for future research include exploring the long-term effects of character education and ensuring consistent, standardized program delivery across diverse educational settings.